Disability and inclusive education - Junior Lopes, Marisa; Mancussi e Faro, Ana Cristina (O Mundo da Saúde, 2006)
The central question was the duality between exclusion and inclusion, for this article examines the admission, the perma- nence and the conclusion of undergraduate course by students with deficiencies in a public institution of Sao Paulo. The objectives were to make a profile of the students; verify the occurrence of deficiencies; identify pedagogical resources for inclusion; know architectural, pedagogical and posture barriers that difficult the performance of the students; to collect suggestions from the students. This was an exploratory study, using an exploratory and quantitative approach. Data gathering was carried through with students of the studied courses using a questionnaire. Regarding the occurrence of deficiencies, we verified 58,9% students with some visual deficiency, 5,2% with physical deficiencies and 1,6% with auditory deficiency. We identified the existence of architectural and pedagogical barriers to the way people act that makes difficult the performance of the students. We believe this study will contribute by offering data for university teachers to deal and welcome diversity in their education practice.